HUBUNGAN BEBAN KERJA DENGAN KINERJA BIDAN KONSELOR ASI DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Mina Yumei Santi; Nur Djanah; Margono Margono (Kesmas Indonesia, 2016)
Coverage of exclusive breastfeeding in Yogyakarta province has reached 67.9% in 2013 but is still did not reach the scope of the national target (80%). One of the factors that influence the success of exclusive breastfeeding is the support of health professionals and breastfeeding counselor which is already available in many areas of health care. It is estimated that high workload caused the performance of midwife counselor of breastfeeding performance becomes low. The aim of this research was to determine the relationship of workload with the performance of midwife breastfeeding counselor in Yogyakarta. This method is quantitative analytical research with cross sectional approach from August-November 2014. This research was made using NASA-TLX (Task Load Index) questionnaire. Sample was determined total population of 45 midwive counselor of breastfeeding. The independent variables is workload and the dependent variable is midwife counselor’s performance. Data analysis using univariate, bivariate analysis with significance level of 5%. The average age of midwife counselor of breastfeeding is 38.71 years, 84.4% educated Diploma-III of Midwifery. The average length of time working as breastfeeding counselor’s is is 43.20 months. Pearson correlation test results showed there was no relationship between workload with the performance of midwife counselor of breastfeeding (p=0.144>0.05)